Ornament and figure in Graeco-Roman art: rethinking visual ontologies in classical antiquity - Dietrich, Nikolaus; Squire, Michael (De Gruyter, 2018)
How does ‘decoration’ work? What are the relations between ‘figurative’ and ‘ornamental’ modes? And how do such modern western distinctions relate to other critical traditions? While these questions have been much debated among art historians, our book offers an ancient visual cultural perspective. On the one hand, we argue, Greek and Roman materials have proved instrumental in shaping modern assumptions. On the other hand, those ideologies are fundamentally removed from ancient ideas: an ancient perspective can therefore shed light on larger aesthetic debates about what images are – or indeed what they should be.This anthology of specially commissioned essays explores a variety of case studies (both literary and art historical alike): it discusses materials from across the ancient Mediterranean, and from Geometric art all the way through to late antiquity; the book also tackles questions of ‘figure’ and ‘ornament’ in relation to different media – including painting, free-standing statues, relief sculpture, mosaics and architecture. A particular feature of the volume lies in bringing together different national academic traditions, building a bridge between formalist approaches and broader cultural historical perspectives
Beiträge teilweise deutsch, teilweise englisch
Keywords: Konferenzschrift -- 2015 -- Berlin; Aufsatzsammlung; Figur; Ornament; Römisches Reich; Griechenland